Commuting pattern of industrial laborers in the Istanbul metropolitan area - Ocakci, M. (Elsevier BV, 2000)
Abstract Using sample data collected in 1997, this paper explores the connection between the location of industries in Istanbul and the residences of their workers in relation to distance, trip duration and mode. It is found that as production sites have moved, so have workers, and unplanned transportation patterns have resulted.